2020
DOI: 10.1039/d0pp00047g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and exploration of excited state assisted two-photon absorption properties of D–A–D type thiophene–pyridine derivatives

Abstract: Diagrammatic representation of excited state assisted two-photon absorption (2PA) behavior of a donor–acceptor type conjugated polymer (P2TPy) exhibiting an extremely low optical limiting threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…This is mainly attributed to the improved ICT, increased polarity and extended conjugation existed due to the presence of bulkier end groups (triphenylamine/carbazole) in the present molecules compared to thiophene/phenyl acrylonitriles. Moreover, the LT value of 2TPA-TPY (1.73 J cm À 2 ) is similar to that of our previously reported polymer, P2TPy (1.42 J cm À 2 ) [44] which suggests that the proper selection of bulkier end group and structural modifications in small molecules could lead to comparable NLO properties as that of polymers and could replace the polymeric materials in optical limiting devices. From the literature reports it is noticed that the enhancement in the nonlinearity is mainly due to the doping of organic compounds with some inorganic materials with the exception of some of the pure organic materials, which showed improved nonlinearity without any doping.…”
Section: Optical Limiting (Ol) Studiessupporting
confidence: 86%
See 2 more Smart Citations
“…This is mainly attributed to the improved ICT, increased polarity and extended conjugation existed due to the presence of bulkier end groups (triphenylamine/carbazole) in the present molecules compared to thiophene/phenyl acrylonitriles. Moreover, the LT value of 2TPA-TPY (1.73 J cm À 2 ) is similar to that of our previously reported polymer, P2TPy (1.42 J cm À 2 ) [44] which suggests that the proper selection of bulkier end group and structural modifications in small molecules could lead to comparable NLO properties as that of polymers and could replace the polymeric materials in optical limiting devices. From the literature reports it is noticed that the enhancement in the nonlinearity is mainly due to the doping of organic compounds with some inorganic materials with the exception of some of the pure organic materials, which showed improved nonlinearity without any doping.…”
Section: Optical Limiting (Ol) Studiessupporting
confidence: 86%
“…Further, Mi et al [48] synthesized Zn-complexed D-π-A type porphyrin derivative, PorÀ ZnÀ N, through [2 + 2] click reactions and studied the NLO response of the material, which showed RSA with β eff of 4.8 × 10 À 10 m W À 1 . Specifically, 2TPA-TPY and 2CBZ-TPY of the present study having similar structural arrangement as that of our previously reported molecules wherein the same core structure (i. e., TPY) was connected to small end groups such as thiophene/phenyl acrylonitriles, [44] show enhanced NLO properties compared to the previous molecules. This is mainly attributed to the improved ICT, increased polarity and extended conjugation existed due to the presence of bulkier end groups (triphenylamine/carbazole) in the present molecules compared to thiophene/phenyl acrylonitriles.…”
Section: Optical Limiting (Ol) Studiessupporting
confidence: 81%
See 1 more Smart Citation
“…1 H NMR (Bruker, 400 MHz), 13 C NMR (Bruker, 100 MHz), ESI-Mass (Waters micro mass Q-Tofmicro) and MALDI-TOF Mass (Autoflex speed MALDI-TOF MS) spectral techniques were utilized to elucidate the structures of all the intermediates and final compounds. A flash EA-112 CHNS analyzer (Thermo electron corporation) was used for the elemental analysis.…”
Section: General Methodsmentioning
confidence: 99%
“…The procedure for the synthesis and the structure characterization data are provided in Supporting Information. Solvent free one pot multicomponent reaction under microwave irradiation yielded the core moiety 3 [13], the alkylation of which yielded the intermediate which was formylated to obtain intermediate 5. The ultraviolet-visible (UV-vis) absorption and photoluminescence (PL) spectra of TPA-TPy and TPA-Py-PTZ in solution (chloroform) were characterized.…”
Section: Synthesis Absorption and Emission Propertiesmentioning
confidence: 99%